EFFORTS TO IMPROVE SOCIAL EMOTIONAL INTELLIGENCE THROUGH PLANTING ACTIVITIES FOR CHILDREN AGED 5-6 YEARS AT PGRI SRIKANDI BALAK KINDERGARTEN, SONGGON DISTRICT, BANYUWANGI IN THE 2023/2024 ACADEMIC YEAR - Dewi Safitri Dewi Safitri; Zahro Ianatuz; Suwargono Trio (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
This study aims to improve the social emotional intelligence of children aged 5-6 years through farming activities with a focus on developing effective and enjoyable alternative learning methods. The problems underlying this study are the low level of children's social emotional intelligence, the limited variety of learning methods that can integrate social emotional aspects with practical activities, and the less than optimal use of planting activities as a learning medium in schools. Through the implementation of planting activities, this study attempts to provide solutions to these problems by creating direct learning experiences that can stimulate children's social emotional development optimally. This study uses the Classroom Action Research (CAR) methodology which is carried out in two cycles, where each cycle consists of the planning, implementation, observation, and reflection stages. The subjects of the study were children aged 5-6 years at PGRI Srikandi Balak Kindergarten, totaling 15 children. The data collection technique used structured observation with observation sheets, documentation, and interviews. The data were analyzed using qualitative and quantitative descriptive analysis techniques. Based on the research and discussion that has been carried out, farming has proven to be effective in improving social emotional intelligence in children aged 5-6 years at PGRI Srikandi Balak Kindergarten